Evaluating the effect of low-density inhomogeneities: A comparative study of lithium fluoride detectors, radiochromic films, and collapsed cone algorithm in 6 MV photon beams - Silveira, Anna Luiza Fraga da; Araújo, Fernanda da Silva Gonçalves; Calheiro, Daniel Silva; Tavares e Silva, André Luiz; Rodrigues Gonçalves, Bruno; Souza Castro, André Lima de; Nolasco, Arnie Verde; Meira-Belo, Luiz Claudio (Applied radiation and isotopes, 2023)
In recent years, there has been significant advancement in the development of physical simulators for dose evaluation. Many dosimetric studies employ solid materials, equivalent to human tissues, to evaluate dose distribution. This study aims to evaluate the effectiveness of inhomogeneity correction carried out by the Monaco/Elekta radiotherapy planning software. To achieve this goal, a physical simulator was created using cork boards to simulate lung tissue and solid water to represent other tissues. This simulator was combined with a dosimetric system that utilized lithium fluoride thermoluminescent detectors - RADOS MTS-N (LiF:Mg,Ti). The thermoluminescent detectors were positioned at various depths using a precisely drilled 2.0 mm thick acrylic plate, and they were placed at predefined positions. The irradiation of the simulator was conducted using an Elekta Synergy® Platform accelerator, employing a 6 MV photon beam with a field size of 15 × 15 cm2 and a source-surface distance (SSD) of 97.5 cm. A radiation dose of 200 cGy was applied for this study. In addition to the dosimetric assessment using thermoluminescent detectors, GAFCHROMIC™ EBT-3 Dosimetry Films were utilized to evaluate the dose at the same measurement points. The dose distribution data measured with the detectors were compared with the values provided by the planning system (TPS) and the inhomogeneity correction was verified. The results support the hypothesis that there is a lack of precision in the analytical simulations performed by the TPS, particularly in cases involving dose distribution at interfaces with varying densities. •Built of a physical phantom using the combination of cork and solid water.•Study of radiological and physical properties of cork and solid water.•Dosimetry in a 6 MV photon beam with TLD MTS and radiochromic films.•Study of inhomogeneity correction of radiotherapy planning software.